√3√5
2√37
-2
-1
Correct answer is D
(1√5+√3−1√5−√3)×1√3
1√5+√3−1√5−√3
(√5−√3)−(√5+√3)(√5+√3)(√5−√3)
= √5−√3−√5−√35−√15+√15−3
= −2√32
= −√3
\therefore (\frac{1}{\sqrt{5} + \sqrt{3}} - \frac{1}{\sqrt{5} - \sqrt{3}}) \times \frac{1}{\sqrt{3}} = - \sqrt{3} \times \frac{1}{\sqrt{3}}
= -1
If x = 3 and y = -1, evaluate 2(x^2 - y^2)...
Solve the equation 3 + 5x - 2x2 = 0...
Find y, if \sqrt{12}-\sqrt{147}+y\sqrt{3} = 0 ...
Find a positive value of \alpha if the coordinate of the centre of a circle x^2 + y\(^2...
If the equations x^2 - 5x + 6 = 0 and x + px + 6 = 0 have the same roots, find the value of p....
Make U the subject of the formula S = \sqrt{\frac{6}{u} - \frac{w}{2}}...